A COMPARATIVE STUDY OF DIFFERENT PRACTICES IN ENVIRONMENTAL IMPACT ASSESSMENT - Romianingsih, Ni Putu Wulan; Utomo, Suyud Warno; Hamzah, Udi Syahnoedi (Journal of Environmental Science and Sustainable Development, 2023)
Currently, there are two practices to assess the environmental and social impacts of the power development projects in Indonesia, namely Indonesia Environmental Impact Assessment (EIA) or Amdal and Environmental and Social Impact Assessment (ESIA) based on the International Finance Corporation (IFC) Performance Standards. However, the ESIA practices in Indonesia, in particular, have yet to be thoroughly examined in the academic context. This research compares the procedural features and environmental and socio-economic aspect coverage of Indonesia's EIA against the IFC (IFC PS) ESIA. A document analysis was employed to systematically analyze the main divergences and similarities contrasted with applicable Indonesian regulations and IFC PS. The results show distinctive differences between Indonesia's EIA and ESIA regarding screening, public participation, scoping, the study of alternatives, impact analysis, review and decision-making, environmental management plans and follow-up, and complementary parallel studies. The research also found that EIA is lacking in covering aspects of ecosystem services, labor, groundwater, landscape and visual impacts, cultural heritage, community safety and security, and non-routine activity or unplanned events. The identified gaps could suggest improvement to ensure Indonesia's EIA and ESIA practices in Indonesia align and provide benefits for sustainable development.